Buddy Program Untuk Pencegahan Bullying di SMP Al Mukhlisin Jakarta Barat - Nahuda; Uwes Sanusi; Zulfitria (Universitas Indraprasta PGRI, 2026)
The phenomenon of bullying among high school adolescents is a serious problem that impacts the psychological, social, and academic aspects of students. Therefore, schools need to create a safe, inclusive, and supportive environment through an approach that fosters empathy and solidarity among students. The Buddy Program is presented as a character education innovation that positions students not only as recipients of policies, but also as agents of change in creating a culture of mutual respect and care. This study aims to describe the implementation of the Buddy Program as a bullying prevention strategy at Al Mukhlisin Junior High School (SMP). This study uses a qualitative approach with descriptive methods, through observations of Buddy Program activities, interviews with supervising teachers, students, and the principal, and documentation of activities that support program implementation. The results show that the Buddy Program at SMP Al Mukhlisin is implemented with a mentoring system between students, where senior students become